Evaluation of corn production parameters and their spatial relationship with chemical attributes of the soil (2011)
The characterization of the soil spatial variability allows a better understanding of the relationships between the soil attributes and the environment. The objective of the study was to evaluate the spatial variability of corn production parameters and their relationship with soil chemical attributes. The study was carried out in the municipality of Miranda do Norte (MA, Brazil) in a Typic Plinthaquults. A mesh of 113 points was designed, taking samples at regular distances of 10 m, determining pH, organic material, P, K, Ca, Mg, and exchangeable acidity. The corn production parameters were ear weight, weight of 100 grains, and yield. The results were analyzed by means of descriptive statistics and geostatistical techniques. The pH and the weight of 100 grains were the only attributes with low variability. The sum of the bases did not show spatial dependence. The corn yield and the ear weight showed similar high correlation and spatial dependence. The production parameters showed a significant influence of the soil chemical attributes, principally those that define the acidity and the cations presence. The contour maps allowed the identification of the soil spatial attributes and their relationship to corn yield.